The given question is wrong.
Question:
What is the solution set to the inequality (4x – 3) (2x – 1) ≥ 0?
(A)
![\{x| x\leq 3\ \text {or} \ x\geq 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/his98vm7np9ffkq1057ejj1bn2zy97bn29.png)
(B)
![\{x| x\leq 2\ \text {or} \ x\geq (4)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/71p42llvn4nlom8ovxjwqd73y3zosgldme.png)
(C)
![\{x| x\leq (1)/(2)\ \text {or} \ x\geq (3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rj54m3i6whgyl73e5o1tvqe8p43ph3p9k6.png)
(D)
![\{x| x\leq (-1)/(2)\ \text {or} \ x\geq (-3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kiqhv3jp0fgsiueq1k415vjgkku1rbl8da.png)
Answer:
The solution set to the given inequality is
.
Solution:
Given expression is (4x – 3) (2x – 1) ≥ 0.
Let us take the expression is equal to zero.
(4x – 3) (2x – 1) = 0
By quadratic factor, If AB = 0, then A = 0 or B = 0.
(4x – 3) = 0 or (2x – 1) = 0
Let us take the first factor equal to zero.
⇒ 4x – 3 = 0
⇒ 4x = 3
![$x=(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lhitx4rkzcld6ref4ktdrujzoh2ruybqdy.png)
Now, take the second factor equal to zero.
⇒ 2x – 1 = 0
⇒ 2x = 1
![$x=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fhduoncwzy666mcgcwcgjx1jv37yiqj0yz.png)
So,
.
Now, write it in the inequality to make the statement true.
![$x\geq (1)/(2)\ \text{(or)}\ x\leq (3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vdlqw83ug92by1yl8ga2l8nh2yrijisxt3.png)
Option C is the correct answer.
The solution set to the given inequality is
.